Diabetes mellitus type 2 correction, changes in c-peptidemia and insulinemia inconnection with ileoduodenoplasty - S. E. Podpryatov; S. S. Podpryatov; N. M. Starchak; A. V. Antonova; I. V. Satsyuk; V. P. Korchak (Сучасні медичні технології)
Purpose of the study. The diabetes move changes estimate and c-peptidemia and insulinemia levels changes in connection with ileoduodenoplasty.